ANALYSIS OF INDEPENDENCE RATIO, PAD EFFECTIVENESS RATIO AND GROWTH RATIO IN LOMBOK CENTRAL REGENCY BUDGET REALIZATION REPORT - Siti Raehanun Shalehah; Saras Handiani; Trisna Wahyunita; Maizatun Nurul Faizah; Yona Oktaviana (Laboratorium Riset Ekonomi, 2022)
With direct assistance from the central government, it does not mean that local governments do not have an active role in supporting management performance in an area. Therefore, to review the performance of the government with the object of study in the Central Lombok Regency area, the author tried to calculate several ratio analyses such as, independence ratio, effectiveness ratio and growth ratio. This study aims to provide a significant overview of the information presented in the financial statements and performance of the regional government of Central Lombok Regency. This research uses descriptive quantitative research to describe and analyze the data that has been obtained. The type of data used is secondary data. As for the results of the analysis of the regional financial performance ratio of Central Lombok Regency in 2018-2021, it can be concluded that in general the performance of regional financial management and the level of regional independence are still not good because the ratio value from year to year is very volatile. This can be seen from several regional financial performance ratios, namely the ratio of regional financial independence, the effectiveness ratio, and the growth ratio which has increased and decreased very significantly.